The N-terminal tail of hERG contains an amphipathic α-helix that regulates channel deactivation. - Chai Ann Ng (Public Library of Science (PLoS), 2011)
The cytoplasmic N-terminal domain of the human ether-a-go-go related gene (hERG) K+ channel is critical for the slow deactivation kinetics of the channel. However, the mechanism(s) by which the N-terminal domain regulates deactivation remains to be determined. Here we show that the solution NMR structure of the N-terminal 135 residues of hERG contains a previously described Per-Arnt-Sim (PAS) domain (residues 26-135) as well as an amphipathic α-helix (residues 13-23) and an initial unstructured segment (residues 2-9). Deletion of residues 2-25, only the unstructured segment (residues 2-9) or replacement of the α-helix with a flexible linker all result in enhanced rates of deactivation. Thus, both the initial flexible segment and the α-helix are required but neither is sufficient to confer slow deactivation kinetics. Alanine scanning mutagenesis identified R5 and G6 in the initial flexible segment as critical for slow deactivation. Alanine mutants in the helical region had less dramatic phenotypes. We propose that the PAS domain is bound close to the central core of the channel and that the N-terminal α-helix ensures that the flexible tail is correctly orientated for interaction with the activation gating machinery to stabilize the open state of the channel.